2018
DOI: 10.1371/journal.pone.0205501
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of CSF cytokine profiles in discriminating infectious from non-infectious CNS disorders

Abstract: Current laboratory testing of cerebrospinal fluid (CSF) does not consistently discriminate between different central nervous system (CNS) disease states. Rapidly distinguishing CNS infections from other brain and spinal cord disorders that share a similar clinical presentation is critical. New approaches focusing on aspects of disease biology, such as immune response profiles that can have stimulus-specific attributes, may be helpful. We undertook this preliminary proof-of-concept study using multiplex ELISA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…[24][25][26] At that stage, also CSF oligoclonal IgG bands and kappa light chains predict the evolution to MS. 26,27 Microglia secrete a number of the selected cytokines or chemokines, and PET studies revealed extensive microglia activation in normal-appearing white matter in MS. infections. 32 The authors correlated it with the treatment response in chronic hepatitis C infections. 33 Furthermore, the IP-10 level was elevated in both the sera and CSF from patients with relapsing-remitting and secondary progressive MS. 34 IP-10 levels predicted MS activity at different time points, and it was higher in patients that converted from CIS to MS than in those that did not convert.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] At that stage, also CSF oligoclonal IgG bands and kappa light chains predict the evolution to MS. 26,27 Microglia secrete a number of the selected cytokines or chemokines, and PET studies revealed extensive microglia activation in normal-appearing white matter in MS. infections. 32 The authors correlated it with the treatment response in chronic hepatitis C infections. 33 Furthermore, the IP-10 level was elevated in both the sera and CSF from patients with relapsing-remitting and secondary progressive MS. 34 IP-10 levels predicted MS activity at different time points, and it was higher in patients that converted from CIS to MS than in those that did not convert.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of PSMs in human CSF and prepare for the potential increases in CNS CA-MRSA infection, it is necessary to study the MRSA growth characteristics that are exclusively present in the CNS environment. CSF is the best representative for pathological CNS changes owing to its close anatomical relationship with critical CNS structures [15]. Thus, the MRSA culture characteristics observed in CSF would be almost identical to those shown in the CNS environment.…”
Section: Introductionmentioning
confidence: 90%
“…The proximity of CSF to the CNS makes it a good target for studying the pathophysiology of CNS diseases. Because CSF serves as a conduit for inflammatory mediators and signaling proteins released during changes in the CNS environment, CSF analysis provides crucial information in the diagnosis of CNS diseases [15,[21][22][23]. Many compounds do not distribute homogeneously in the CSF space and this non-uniform distribution of compounds within the CSF space has clinical significance because the ratio of bacterial cell aggregation varies with the different CSF compartments [24].…”
Section: Csf As a Spokesman For The Cns Environmentmentioning
confidence: 99%
“…The cerebrospinal fluid (CSF) is a bodily fluid that surrounds the brain and serves an array of functions ranging from acting as a shock absorber from neurological trauma to circulating nutrients around the CNS. Its role in homeostasis and neurological metabolism has made it a great reporter of the neurological environment; therefore, it can be clinically used to detect infectious agents and diseases (25). Furthermore, viral implications on the immune system could induce indirect effects on the CNS.…”
Section: Neurological Impact Central Nervous Systemmentioning
confidence: 99%